Evaluation of techniques for diagnosis of Trypanosoma vivax infections in naturally infected cattle in the Zona da Mata Mineira - Alcindo, Jefferson Filgueira [UNESP]; Vieira, Maria Clara Guimarães; Rocha, Thamiris Vilela Pereira; Cardinot, Cinthya Brillante; Deschk, Maurício; Amaral, Gláucia Guimarães; de Araujo, Rafael Ferreira; Franciscato, Carina; Neto, Kayo José Garcia de Almeida Castilho [UNESP]; Machado, Rosângela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (FapUNIFESP (SciELO), 2022)
This study aimed to evaluate diagnostic techniques for trypanosomiasis, caused by Trypanosoma vivax, in naturally infected cattle in Minas Gerais, Zona da Mata. The deaths of six lactating cows with similar clinical conditions— characterized by hyporexia, hypogalactia, and recumbency—had been reported from one property. Initially, two animals were examined and diagnosed with trypanosomiasis through identification of the protozoan in a blood smear. After the initial diagnosis, all lactating cows (n=37) on the property were examined, and blood samples were collected for tests including whole blood smear, buffy coat smear, Woo’s technique, enzyme-linked immunosorbent assay (ELISA), and polymerase chain reaction (PCR). Woo’s test, buffy coat smears, and whole blood smears indicated that 4/37 (10.81%) animals were positive for trypanosomiasis, whereas ELISA and PCR indicated that 33/37 (89.19%) and 27/37 (72.97%) animals, respectively, were positive. The agreement obtained between parasitological techniques was classified as high, while between ELISA and PCR, no agreement. In conclusion, parasitological techniques have a low capacity to identify infected animals in the chronic stage of T. vivax infection. Therefore, techniques such as PCR and/or ELISA should be used to minimize the occurrence of false negatives.
Avaliação de técnicas para diagnóstico de infecções por Trypanosoma vivax em bovinos naturalmente infectados na Zona da Mata Mineira
Keywords: Dairy cattle; Diagnosis; Laboratory techniques; Trypanosomiasis